2007
DOI: 10.1111/j.1464-5491.2007.02087.x
|View full text |Cite
|
Sign up to set email alerts
|

Common polymorphisms of the PAI1 gene do not play a major role in the development of diabetic nephropathy in Type 1 diabetes

Abstract: It is unlikely that common polymorphisms of thePAI1 gene strongly influence susceptibility to diabetic nephropathy in the White Type 1 diabetic population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…Ten studies were included in the qualitative synthesis of meta-analysis, which contained 1366 cases and 1888 controls. [7][8][9][10][11][12][13][14][15][16] All the studies were case-control studies. [7][8][9][10][11][12][13][14][15][16] Among these studies, three were from the Europe, 8,9,11 and seven 7,10,[12][13][14][15][16] were from Asian countries.…”
Section: Trial Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies were included in the qualitative synthesis of meta-analysis, which contained 1366 cases and 1888 controls. [7][8][9][10][11][12][13][14][15][16] All the studies were case-control studies. [7][8][9][10][11][12][13][14][15][16] Among these studies, three were from the Europe, 8,9,11 and seven 7,10,[12][13][14][15][16] were from Asian countries.…”
Section: Trial Characteristicsmentioning
confidence: 99%
“…The ethnicities included East Asians 7,10,12-16 and Caucasians. 8,9,11 Three studies reported the results in Type-1 DM, 8,9,11 while the rest seven studies 7,10,[12][13][14][15][16] in Type-2 DM. The characteristics of each study included were shown in Table 1.…”
Section: Trial Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations